Leadership in charitable non-government organisations (NGO's): Integrating individual and organisational beliefs - Morris, Charlotte Lucy (Curtin University, 2006)
The exploration of the four key themes of leadership, spirituality, ethics and values and their relationship between and with employers and employees in human service charitable NGOs in Perth, Western Australian, provided the main purpose for the current research. In addition, the purpose included examining the impact of charities operating as if they were for-profit businesses; the impact of faith and secularity on the work of charities; and possible gender differences arising from the themes within this context. The qualitative research was undertaken using hermeneutic phenomenological methodology; however, feminism, post-modernism and narrative practices were used to elicit additional perspectives from the resulting material. The current research used a broad-ranging, multi-disciplinary approach, thus encompassing a literature review of the philosophical, ethical, psychological, theological and anthropological disciplines as it tracked some of the material’s substantial heritage. Additionally, the research focussed on the experience of charitable workplace cultures which provide the context for the delivery of human services, and discussed the current charitable human services paradigm. A total of 46 individuals from 8 different charities participated through in-depth interviews. They included organisational leaders, management and front-line workers who provided collectively and individually a rich mine of material for exploration and discovery from which to unravel the essence of the responses.The emerging conclusions provide the capacity to view the charitable organisation from a gendered perspective, as female, thus reflecting the profile of the workforce; while also uncovering substantial discrimination and inequity in employment conditions. Leadership styles were gendered, as were the discourses on ethics, values and spirituality. Organisational size was a key factor in determining values and changing perspectives matched more closely, the business paradigm. The faith and secularity of each NGO also presented opportunities to map organisational intention around leadership, spirituality, ethics and values such that further research opportunities have been highlighted across the results.